2017
DOI: 10.1051/matecconf/201712103015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fatigue testing on the properties of Glass-Epoxy composites using the acoustic tool

Abstract: Abstract. This study presents the experimental results of the influence of mechanical fatigue on composite material. The plates of Glass fiber with SR 1500 epoxy resin with SD 2505 composite were realized by vacuum molding. Experimental tests were carried out on a standard hydraulic machine INSTRON 8516. The machine is interfaced with a dedicated computer for controlling and data acquisition. The fatigue tests were performed using sinusoidal type of waveform at a displacement control with frequency of 10 Hz. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The crack and delaminating appears in the samples as a result of shear stresses in the layers which is characteristic of bending test [10]. [11]. Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The crack and delaminating appears in the samples as a result of shear stresses in the layers which is characteristic of bending test [10]. [11]. Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, water absorption increases with the conditioning period. 14 Furthermore, the environmental effect of carbon/venylester composites under flexural fatigue shows fatigue life degradation; however, the morphology of the damaged region reveals a similarity between the dry and seawaterconditioned samples. 15 In addition, the microstructural behavior of composites under bending/flexural loading has been investigated by different researchers to formulate the fracture criteria of fiber-reinforced composites.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of research were conducted to replace ship components with corrosion-resistant materials, like composites. 14,[22][23][24][25][26][27] Among these, Wei et al 28 investigated the effect of a corrosive environment (seawater treatment) on the tensile and bending of basalt/epoxy and glass/epoxy composites. The author reported that the mass gain on this composite is due to soluble material withdrawal and water absorption.…”
Section: Introductionmentioning
confidence: 99%